Development of a NC-Controlled GTAW-Based Wire Arc Additive Manufacturing System for Using Friction Stir Extrusion Recycled Wires - Gustavo H. S. F. L. Carvalho; Gianni Campatelli; Bruno Silva Cota; Davide Campanella; Rosa Di Lorenzo (Machines)
This study investigates the feasibility of using friction stir extrusion (FSE) recycled aluminum wires as filler metals for gas tungsten arc welding (GTAW) and additive manufacturing applications. A NC-controlled GTAW feeding system was developed to enable the deposition of these recycled wires. The effect of cleaning the machining chips before the FSE process on the quality of the manufactured wires and the resulting welded beads was evaluated. Wires produced from uncleaned chips and cleaned chips were compared in terms of their external appearance, ductility, and the presence of porosity after the weld deposition. The results showed that cleaning the chips before the FSE process is crucial for obtaining more uniform wires with better ductility. Automatic GTAW deposition using cleaned wires resulted in significantly improved bead geometry, reduced external porosity, and overall better quality compared to uncleaned wires. However, both wire types exhibited internal porosity, with uncleaned wires showing the worst performance. The findings demonstrate the potential of using FSE recycled aluminum wires for welding and additive manufacturing while highlighting the importance of chip cleaning and the need for further optimization to minimize porosity in the deposited material.